2009
DOI: 10.1016/j.ijforecast.2008.07.004
|View full text |Cite|
|
Sign up to set email alerts
|

Hierarchical forecasts for Australian domestic tourism

Abstract: In this paper we explore the hierarchical nature of tourism demand time series and produce short-term forecasts for Australian domestic tourism. The data and forecasts are organized in a hierarchy based on disaggregating the data for different geographical regions and for different purposes of travel. We consider five approaches to hierarchical forecasting: two variations of the top-down approach, the bottom-up method, a newly proposed top-down approach where top-level forecasts are disaggregated according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
216
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(222 citation statements)
references
References 20 publications
1
216
0
5
Order By: Relevance
“…We refer to (5) as the temporal reconciliation regression model. It is analogous to the cross-sectional hierarchical reconciliation regression model proposed by Hyndman et al (2011) and also applied in Athanasopoulos et al (2009) for reconciling forecasts of structures of tourism demand. A similar idea has been used for imposing aggregation constraints on time series produced by national statistical agencies (Quenneville and Fortier, 2012).…”
Section: Forecasting Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…We refer to (5) as the temporal reconciliation regression model. It is analogous to the cross-sectional hierarchical reconciliation regression model proposed by Hyndman et al (2011) and also applied in Athanasopoulos et al (2009) for reconciling forecasts of structures of tourism demand. A similar idea has been used for imposing aggregation constraints on time series produced by national statistical agencies (Quenneville and Fortier, 2012).…”
Section: Forecasting Frameworkmentioning
confidence: 99%
“…In general, Σ is not known and needs to be estimated. Hyndman et al (2011) and Athanasopoulos et al (2009) avoid estimating Σ by using ordinary least squares (OLS), replacing Σ by σ 2 I in (6). This is only optimal under some special conditions, such as when the reconciliation errors are equivariant and uncorrelated, or when the base forecast errors satisfy the same aggregation constraints as the original data (Hyndman et al, 2011), neither of which is likely to be true.…”
Section: Forecasting Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…The second group of combination weights is based on the original aggregation weights. We apply the novel combination strategy proposed by Athanasopoulos et al (2009) and Hyndman et al (2011) and the shrinkage method suggested by Stock and Watson (2004) to derive combination weights that also use information of the original aggregation weights. It should be noticed that one could also try to improve the forecasting performance of the forecast combination by selecting the most accurate forecast model for each countries' time series and then combine them.…”
mentioning
confidence: 99%